2009
DOI: 10.1080/09638280802030923
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of participation in the National Veterans Wheelchair Games and Winter Sports Clinic

Abstract: Recommending veterans participate in events such as the NVWG and WSC can provide psychosocial benefits to veterans with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 22 publications
5
63
0
1
Order By: Relevance
“…Wheelchair athletes in track races compete at a very high level. While older athletes focus more on the psychosocial benefits of sport (Sporner, et al, 2009), younger athletes may be rather more motivated to win (Skordilis, Gavriilidis, Charitou & Asonitou, 2003).…”
Section: Participation Trendsmentioning
confidence: 99%
“…Wheelchair athletes in track races compete at a very high level. While older athletes focus more on the psychosocial benefits of sport (Sporner, et al, 2009), younger athletes may be rather more motivated to win (Skordilis, Gavriilidis, Charitou & Asonitou, 2003).…”
Section: Participation Trendsmentioning
confidence: 99%
“…Participation in adapted sports has been rising steadily as a result of new innovations and the growth of science and technology, with better assistive devices to enhance functional capacity in individuals with disabilities [2,12]. Advancements in science and technology have produced adapted equipment that allows individuals with disabilities to achieve or even surpass records held by nondisabled athletes [2,[12][13]. The role of technology in measuring performance in adapted sports is growing, which could enhance the training efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing the literature, they found that the majority of research was conducted with nondisabled athletes and the results were then compared with individuals with disabilities [11]. Participation in adapted sports has been rising steadily as a result of new innovations and the growth of science and technology, with better assistive devices to enhance functional capacity in individuals with disabilities [2,12]. Advancements in science and technology have produced adapted equipment that allows individuals with disabilities to achieve or even surpass records held by nondisabled athletes [2,[12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities also help to improve the athlete's self-esteem, quality of life, 8 overall health, 3 self-efficacy, feelings of empowerment, and motivation for continued involvement.…”
mentioning
confidence: 99%